Trends in sports participation in adolescents: Data from a large-scale sample in the US adolescents - Yu Deng; Anhui Fan (Frontiers Media S.A., 2022)
BackgroundAlthough changes in overall physical activity (PA) have been identified in adolescents, the trend in sports participation is still understudied. It is widely believed that monitoring the changes in sports participation is conducive to promote the development of sports activities. The purpose of this research was to identify the changes in sports participation in adolescents over the past years.MethodsThis research selected secondary data from 2011, 2013, 2015, 2017, and 2019 Youth Risk Behavior Surveillance (YRBS). Logistic regression models were applied to discuss and analyze the secular changes across the years of data. The change differences in sports participation by sex, grade, and race/ethnicity were also explored via separate logistic regression.ResultsA declined overall trend could be observed in sports participation in adolescents, the prevalence of sport participation was 58.4% in 2011 and 57.4% in 2019. The declining trend was also observed in grades 10 (62.3% in 2011 and 57.9% in 2019) and 12 (52.5% in 2011 and 49.8% in 2019) adolescents, and an increase could be observed in grade 11 (56.2% in 2011 and 59.1% in 2019) adolescents, but few changes were found in grade 9 (61.4% in 2011 and 61.9% in 2019) adolescents. Only white adolescents reported an increasing prevalence of sports participation, slight declines in sports participation were observed in black or African American, Hispanic/Latino, and other adolescents.ConclusionsThe declining trend in sports participation could be seen in adolescents between 2011 and 2019, but it should also note that large variations of trends in sport participation by subgroups were also found.